A biographical dictionary of the twentieth-century Royal Navy - Wilson, Alastair 1934- (Seaforth Publishing, 2013)
Career histories of the 336 most senior Royal Navy officers of the twentieth century The only published biographies of many individuals An essential reference for historians and genealogists